Continuous two‐staged co‐digestion process for biohydrogen production from agro‐industrial wastes. (9th December 2015) - Gomez‐Romero, J.; Gonzalez‐Garcia, R. A.; Chairez, I.; Torres, L.; García‐Peña, E. I.
Summary: Mexico produces large amounts of organic residues. Twenty milliard tons of fruit and vegetable wastes (FVW) are produced yearly. On the other hand, the cheese processing industry produces crude cheese whey (CCW) with an annual production of 1 million metric tons. These types of residues are well characterized, and both constitute a potential feedstock for biohydrogen production, individually or as a mixture. Recently, we demonstrated the feasibility of utilizing CCW and FVW in a co‐digestion process to produce biohydrogen. The possibility to design an effective process in a two stage configuration was evaluated based in our previous studies of the by‐products and description of microbial ecology evolution of the co‐digestion process. An initial assimilation of easily degradable carbohydrates and protein allowed cell growth and acetate and lactate as main byproducts. The co‐digestion and two‐stage processes increased several times the biohydrogen yield compared with those obtained from single substrate and in a co‐digestion single stage process. Higher biohydrogen productivity was a result of reaction stability in comparison to single‐substrate digestion and one‐stage processes. The effect of hydraulic retention time (HRT) and organic loading rate (OLR) on the volumetric hydrogen production rate (VHPR) and yield (YH2 ) was evaluated in a two‐staged co‐digestion process of FVW and CCW. The system consisted of hydrolytic and hydrogenic bioreactors operated in batch mode and continuous regime (89 days), respectively. Eight conditions of HRTs and respective OLRs were evaluated. As HRT decreased, the VHPR increased proportionally, reaching the highest average values around 7 L L −1 d −1 at an HRT between 15 and 17.5 h. The highest YH2, (813.3 mL H2 g COD −1 ) was determined at 17.5 h (OLR, 80.02 g COD L −1 d −1 ). Based on the distribution of the final products, the processes occur sequentially and reach a steady state set by the OLR. Biohydrogen production is a result of a syntrophic microbial activity. In general, the two stages of the co‐digestion process provided higher stability, reliability, and efficiency. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The effect of hydraulic retention time (HRT) and organic loading rate (OLR) on the volumetric hydrogen production rate (VHPR) and yield (YH2 ) was evaluated in a two‐staged co‐digestion process of fruit and vegetable waste and crude cheese whey. VHPR increased as HRT decreased. The highest VHPR (8 L L −1 d −1 ) and YH2 (813.3 mL H2 g COD −1 ) were obtained at an HRT between 15 and 17.5 h. The process occurs sequentially and reaches a steady state set by the OLR.